Los paradigmas mesoamericanos que unificaron la reconstrucción del pasado: el mito de la creación del cosmos; la fundación del reino maravilloso (Tollán), y Quetzalcóatl, el creador de estados y dinastías - Florescano, Enrique (El Colegio de México, A.C., 2002)
Out of the myths of the creation of the universe, the paradigms that preside Mesoamerican historical  narrative belong to Quetzalcoatl and Tollan. Every account of the creation repeats the story of the arranging of the universe,  the origin of human being and the establishment of kingdoms. Subsequent capitals were founded after the archetype of the primeval Tollan. Quetzalcoatl, as well, remains as the leading  reference in matters  of authority and government. Thus, the obsession of Mesoamerican societies is with the repetition of the initial archetype and the nullification of time and his- tory through the device of the perpetual return to the origin.